VARIASI LAMA FERMENTASI TERHADAP MUTU MIKROBIOLOGIS DAN VISKOSITAS SOYGHURT MENGGUNAKAN Lactobacillus plantarum IDY L-20 - FAHMI SEPTIAN SEMBIRING; AKHYAR ALI; EVY ROSSI (Universitas Riau, 2019)
Soyghurt was a probiotic drink made by adding a lactic acid food (LAB) into the soy milk. In general,cultures used was Lactobacillus bulgaricus and Streptococcus thermophilus. This study used L. plantarumcultivated from soybean solid waste so it was assumed to have good growth so as to produce good qualitysoyghurt. The aim of this research was to get the best fermentation time for microbiological quality ofsoyghurt using L. plantarum IDY L-20. This research was conducted experimentally using Randomized CompleteDesign with four treatments and four replications. The treatments in this study were P1, P2, P3, and P4; eachtreatment was fermentation time 8 hours, 16 hours, 24 hours, and 32 hours. The results showed thatfermentation time had significant effect (P <0,05) on pH, viscosity, total acid, total BAL, and total sugar. Thebest treatment for making soyghurt using L. plantarum IDY L-20 was P3 (24-hour fermentation length) withpH (4,14), viscosity (996 cP), total acid (0,88%), total LAB (11,00 log cfu/ml), and total sugar (4,37%). Thelonger time fermentation used will decrease the pH and total sugar while the viscosity, total acid, and totalLAB value will increase. This was because of LAB continues to perform metabolic processes.